N-Terminal Prohormone of Brain Natriuretic Peptide but not C-Terminal Pre-Pro Vasopressin (Copeptin) Level is Associated with the Response to Antihypertensive Therapy in Haemodialysis Patients - Katarzyna Wyskida; Joanna Ficek; Rafał Ficek; Dagmara Adamska; Patrycja Jędrzejowska; Jarosław Wajda; Dariusz Klein; Joanna Witkowicz; Sylwia Rotkegel; Urszula Spiechowicz-Zatoń; Joanna Kocemba-Dyczek; Jarosław Ciepał; et al. (Karger Publishers, 2017)
Background/Aims: Volume overload, frequently clinically asymptomatic is considered as a causative factor limiting the effectiveness of antihypertensive therapy in haemodialysis (HD) patients. Therefore, the aim of this study was to assess plasma levels of N-terminal fragment of the prohormone brain natriuretic peptide (NT-proBNP) and a C-terminal portion of the precursor of vasopressin (CT-proAVP, copeptin), surrogate markers of volume overload in HD patients in relation to the number of antihypertensive drugs used in the hypertension treatment. Methods: One hundred and fifty adult HD patients (92 males) were enrolled into this study. Clinical data concerning blood pressure (BP) measurements prior haemodialysis session and pharmacotherapy were collected from all patients. In addition to routine laboratory parameters, plasma levels of NT-proBNP and CT-proAVP were measured, and daily sodium and water consumption were estimated with a portion-size food frequency questionnaire. Results: Among 145 (96.7%) hypertensive HD patients, 131 were receiving antihypertensive medication. Despite antihypertensive therapy, 31.0% had inadequate BP control. Plasma concentration of NT-proBNP was associated with systolic (R=0.19; p=0.02) but not diastolic BP values and with the number of received antihypertensive drugs (R=0.21; p=0.01). The highest NT-proBNP values were observed in patients receiving 3 or more antihypertensive drugs. In contrast, no significant correlation was found between plasma CT-proAVP concentrations and BP values as well as and the number of antihypertensive drugs. Receiver operator curve analysis showed that NT-proBNP values over 13,184 pg/mL predicted the use of at least 3 antihypertensive drugs in maximal doses in the therapy of hypertension, similar analyses performed for CT-proAVP showed much less specificity. Conclusions: 1. Increased levels of NT-proBNP seems to be a better biomarker of multidrug antihypertensive therapy requirement than CT-proAVP. 2. Whether estimation of NT-proBNP in these patients will be also better biomarker than copeptin in the prediction of cardiovascular complications related to hypertension needs further investigations.